Looking for "interesting people": Chinese gay men's exploration of relationship development on dating apps. (September 2020) - Wu, Shangwei; Ward, Janelle
Mobile dating applications play a prominent role in Chinese gay men's social lives. Based on in-depth interviews with 21 participants, this study explores how urban gay singles in China develop social relationships on dating apps. It reveals that relationship development is often driven by casual conversations, which are not motivated by clear pragmatic purposes. Casual conversations tend to unfold around common hobbies or experiences, serving as a source of sociability, or satisfaction in socializing itself. In contrast to casual conversations, two forms of conversations are deemed highly instrumental and undesirable: one is the sex-oriented conversation aimed at immediate sexual encounters; the other is the interrogative conversation in which people ask private questions in a nonreciprocal and rigid way. Besides craving sociability, users "relationalize" casual sex by perceiving it as a form of social connection and endowing it with the potential to foster a relationship. This is also reflected in users' preference for sexual partners with whom they can hold a conversation. Users also exploit the affordances of different media platforms and capture the relationship potential by platform switching. They switch to the mainstream media platform WeChat for more synchronous communication and to collect more identity cues from each other. Platform switching also signals willingness for relationship development and mutual trust. Nevertheless, users keep going back to dating apps for new possibilities for social relationships.